Burnout in Icelandic companies : do HR managers need stronger preventative measures? - Guðrún Ósk Stefánsdóttir 1994- (2019)
Burnout is a severe condition of psychological strain that results from a persistent response to chronic interpersonal and emotional stressors at work, exceeding the coping resources of the worker. In Iceland, burnout awareness has been increasing significantly. The unions and work rehabilitation foundations are worried about increased sick leave and the increased number of people seeking help because of burnout. Thus, it can be stated that burnout prevention measures need to be stronger in Iceland. The aim of this research was to explore whether human resource (HR) managers in Iceland find current burnout prevention measures sufficient or whether they need stronger measures, e.g. health promotion. I also explore if HR managers feel that the knowledge of burnout symptoms among themselves, other department managers and employees is sufficient, or whether they need more training in this area. This is a qualitative research, in which seven semi-structured interviews were conducted. The participants were closely involved with human resource in their companies; six were human resource directors. The findings revealed that participants lacked sufficient preventative tools and felt the need for more ‘anti-burnout‘information, and burnout training in their company. Furthermore, burnout was usually not measured, so it was hard for participants to say with accuracy whether it was a growing problem in their company.The participants cited as the main factors that hindered them in preventing burnout: uncontrollable stress factors; lack of burnout measurement standards and an accepted definition of burnout; and a generalized absence of appropriate knowledge about burnout and its symptoms. Given the uneven Icelandic business world awareness of this troubling workplace problem and how to deal with it, I recommend additional academic and company investigation into worker burnout and appropriate preventative measures. Keywords: human resource management, workplace stress, burnout, burnout prevention, burnout training and ...